Assessing the influence of the barriers to e-commerce adoption among SMEs in the Philippines - Cecilio, Denise Krisha G. (Animo Repository, 2022)
Electronic commerce (EC) adoption among firms in developing countries remains to be modest in spite of its advantage over traditional markets. Existing literature associates this adoption decision to the technological, organizational, and environmental barriers that a firm experiences. However, while the factors and barriers affecting EC adoption have been widely covered, there exists fewer studies in the context of the Philippines. Given that firms from different countries encounter diverse and distinct bottlenecks, this study identifies the specific barriers that are impeding the adoption of EC among small and medium enterprises (SMEs) in the Philippines. Using a probit regression model, the study utilized pooled firm-level data from the 2013 and 2015 Survey on Information and Communication Technology (SICT) and controls for firm characteristics along with industry effects. The results reveal that the preference to maintain the current business model has the strongest effect in impeding EC adoption among SMEs in the Philippines. This is followed by security and privacy concerns, high costs, unreliable internet connections, insufficient customer demand, uncertainty concerning the legal framework, and computer hardware limitations. Given these results, initiatives that facilitate the changing of mindsets are recommended to be prioritized. For private sector efforts, communication and awareness are to be promoted for adjusting preference. For government agencies, incentivizing adoption through training programs, discounted access to EC technologies, and adequate financing are highly recommended.